Fracture Patterns in Craniofacial Gunshot Wounds: A Seven-Year Experience - Gabriela G. Cruz; Sameer H. Siddiqui; David Z. Allen; Kunal R. Shetty; Sean P. McKee; Brady J. Anderson; Mark Knackstedt; W. Katherine Kao; Tang Ho (Craniomaxillofacial Trauma & Reconstruction)
Objective: To characterize facial fracture patterns and understand predictors of surgical repair and LOS with the objective of assisting providers in managing and understanding these complex injuries. Study Design: This is a retrospective cohort chart review study. Methods: A retrospective review was conducted for patients admitted with gunshot wounds (GSWs) to the head, neck, or face between January 2013 and March 2020 at a level one trauma tertiary care hospital. Univariate and multivariate analysis were performed to identify associations with surgical repair and LOS. Results: Of the 578 patients with head, neck, or facial GSWs, 204 survived and sustained facial fractures. The maxilla (n = 127, 62%), orbit (n = 114, 55%), and mandible (n = 104, 51%) were the most fractured. Operative rates differed by location (p < 0.001) with highest rates for fractures involving the mandible (76%). In univariate analysis, overall facial fracture surgery was associated with transfacial injuries; mandible, palate and nasal fractures; tracheostomy; gastrostomy tube placement; ICU admission; and a longer-than-24 h ICU stay (all p < 0.05). In multivariate analysis, predictors of surgical repair included a length of stay greater than 3 days (OR 2.9), transfascial injury (OR 3.7) and tracheostomy placement (OR 5.1; all p-values < 0.05), while nasal and mandible fractures were also associated with overall operative repair (OR 2.5 and 9.3, respectively; p-value < 0.05 for both). Univariate analysis showed that among patients with GSW injuries who underwent facial plastic reconstructive surgery (FPRS) with comorbid serious polytrauma, the inpatient LOS was predicted solely by the presence of subarachnoid, subdural and intracranial hemorrhage (p-value < 0.005). Subsequent multivariate analysis found that the only predictor for greater hospital LOS for patients who underwent surgical repair was earlier timing to FPRS of less than five days (OR 0.17) and placement of a gastrostomy tube (OR 7.85). Conclusions: Managing facial fractures in GSW patients requires complex medical decision making with a consideration of functional and esthetic outcomes in the context of concomitant injuries and overall prognosis. Certain characteristics such as ICU admission, longer hospital stay, trajectory of GSW, tracheostomy placement, and specific operative locations are associated with higher rates of operative repair. Inpatient hospitalization LOS for patients who underwent FPRS was predicted by timing from admission to surgical repair.